The Effect of Implementing Work Ethics and Islamic Leadership on Employee Performance - Lestari, Rini; Nurjaya, Dimas; Wahyuningtyas, Innez Assyffa Andien (Research Synergy Foundation, 2023)
The performance of employees in a company is a parameter of success in realizing the vision and mission to achieve the goals of a company. Poor employee performance stems from a lack of implementation of work ethics and leadership. For a Muslim, work ethics and Islamic leadership are matters relating to the actions, attitudes, and attributes that a person performs and considers work as worship for Allah SWT and it is based on the Al-Quran and Hadith to get grace and a better quality of life. The purpose of this study was to determine the influence of the application of Islamic work ethics and Islamic leadership on the performance of employees at the Bandung Islamic University Foundation. The research method used in this study is a survey method with a quantitative approach. The data source used in this study is primary data. The sampling technique in this study is non-probability sampling with a convenience sampling technique. The results of this study state that the Application of Islamic Work Ethics and Islamic Leadership influences Employee Performance.